Jump to content

Unsupervised Learning: Difference between revisions

(19 intermediate revisions by the same user not shown)
Line 77: Line 77:
</math><br>
</math><br>
<math>
<math>
\implies \log\left[E_{Q}\left(\frac{Pr(x^{(i)}, q^{(i)}; \theta)}{Q^{(i)}_{(j)}}\right)\right] \geq E_{Q} \left[ \log \left(\frac{Pr(x^{(i)}, q^{(i)}; \theta)}{Q^{(i)}(j)} \right)\right]
\implies \log\left[E_{Q}\left(\frac{P(x^{(i)}, q^{(i)}; \theta)}{Q^{(i)}_{(j)}}\right)\right] \geq E_{Q} \left[ \log \left(\frac{P(x^{(i)}, q^{(i)}; \theta)}{Q^{(i)}(j)} \right)\right]
</math><br>
</math><br>
Let <math>J(\theta, Q) = \sum_{i=1}^{m} \sum_{j=1}^{k} Q^{(i)}_{(j)} \log \left( \frac{Pr(x^{(i)}, z^{(i)}=j;\theta)}{Q^{(i)}(j)} \right)</math><br>
Let <math>J(\theta, Q) = \sum_{i=1}^{m} \sum_{j=1}^{k} Q^{(i)}_{(j)} \log \left( \frac{P(x^{(i)}, z^{(i)}=j;\theta)}{Q^{(i)}(j)} \right)</math><br>
The EM algorithm is an iterative algorithm which alternates between an E-Step and an M-Step.
The EM algorithm is an iterative algorithm which alternates between an E-Step and an M-Step.
=====E-Step=====
=====E-Step=====
Line 88: Line 88:
This implies <math>Q^{(i)}(j) = c * P(x^{(i)}, z^{(i)} = j ; \theta)</math>.<br>
This implies <math>Q^{(i)}(j) = c * P(x^{(i)}, z^{(i)} = j ; \theta)</math>.<br>
Since Q is a pmf, we have <math>Q^{(i)}(j) = \frac{1}{P(x^{(i)})} * P(x^{(i)}, z^{(i)} = j ; \theta) = P(z^{(i)} ; x^{(i)}, \theta)</math><br>
Since Q is a pmf, we have <math>Q^{(i)}(j) = \frac{1}{P(x^{(i)})} * P(x^{(i)}, z^{(i)} = j ; \theta) = P(z^{(i)} ; x^{(i)}, \theta)</math><br>
Q is updated with <math>Q^{(i)}(j) = \frac{Pr(z^{(i)}=j)Pr(x^{(i)}|z^{(i)}=j)}{Pr(x^{(i)})}</math>
Q is updated with <math>Q^{(i)}(j) = \frac{P(z^{(i)}=j)P(x^{(i)}|z^{(i)}=j)}{P(x^{(i)})}</math>
{{hidden | Maximization w.r.t Q |
{{hidden | Maximization w.r.t Q |
<math>J(\theta, Q) = \sum_{i=1}^{m} \sum_{j=1}^{k} Q^{(i)}_{(j)} \log \left( \frac{Pr(x^{(i)}, z^{(i)}=j;\theta)}{Q^{(i)}(j)} \right)</math><br>
<math>J(\theta, Q) = \sum_{i=1}^{m} \sum_{j=1}^{k} Q^{(i)}_{(j)} \log \left( \frac{P(x^{(i)}, z^{(i)}=j;\theta)}{Q^{(i)}(j)} \right)</math><br>
We are assuming that Q is a pmf so <math>\sum_j Q = 1 </math><br>
We are assuming that Q is a pmf so <math>\sum_j Q = 1 </math><br>
Our lagrangian is:<br>
Our lagrangian is:<br>
<math>
<math>
\max_{Q} \min_{\beta} \left[ \sum_{i=1}^{m} \sum_{j=1}^{k} Q^{(i)}_{(j)} \log \left( \frac{Pr(x^{(i)}, z^{(i)}=j;\theta)}{Q^{(i)}(j)} \right) +\beta (\sum_j Q^{(i)}_{(j)} - 1)\right]
\max_{Q} \min_{\beta} \left[ \sum_{i=1}^{m} \sum_{j=1}^{k} Q^{(i)}_{(j)} \log \left( \frac{P(x^{(i)}, z^{(i)}=j;\theta)}{Q^{(i)}(j)} \right) +\beta (\sum_j Q^{(i)}_{(j)} - 1)\right]
</math>
</math>
We can maximize each <math>Q^{(i)}</math> independently.<br>
We can maximize each <math>Q^{(i)}</math> independently.<br>
Taking the derivative wrt Q we get:<br>
Taking the derivative wrt Q we get:<br>
<math>
<math>
\frac{\partial}{\partial Q^{(i)}_{(j)}} \sum_{j=1}^{k} Q^{(i)}_{(j)} \log \left( \frac{Pr(x^{(i)}, z^{(i)}=j;\theta)}{Q^{(i)}(j)} \right) +\beta (\sum_j Q^{(i)}_{(j)} - 1)
\frac{\partial}{\partial Q^{(i)}_{(j)}} \sum_{j=1}^{k} Q^{(i)}_{(j)} \log \left( \frac{P(x^{(i)}, z^{(i)}=j;\theta)}{Q^{(i)}(j)} \right) +\beta (\sum_j Q^{(i)}_{(j)} - 1)
</math><br>
</math><br>
<math>
<math>
= \log(\frac{Pr(x^{(i)}, z^{(i)}=j;\theta)}{Q}) - Q \frac{Q}{Pr(x^{(i)}, z^{(i)}=j;\theta)} (Pr(x^{(i)}, z^{(i)}=j;\theta))(Q^{-2}) + \beta
= \log(\frac{P(x^{(i)}, z^{(i)}=j;\theta)}{Q}) - Q \frac{Q}{P(x^{(i)}, z^{(i)}=j;\theta)} (P(x^{(i)}, z^{(i)}=j;\theta))(Q^{-2}) + \beta
</math>
</math>
</math><br>
</math><br>
<math>
<math>
= \log(\frac{Pr(x^{(i)}, z^{(i)}=j;\theta)}{Q}) - 1 + \beta = 0
= \log(\frac{P(x^{(i)}, z^{(i)}=j;\theta)}{Q}) - 1 + \beta = 0
</math><br>
</math><br>
<math>
<math>
\implies Q^{(i)}_{(j)} = (\frac{1}{exp(1-\beta)})Pr(x^{(i)}, z^{(i)}=j;\theta)
\implies Q^{(i)}_{(j)} = (\frac{1}{exp(1-\beta)})P(x^{(i)}, z^{(i)}=j;\theta)
</math><br>
</math><br>
Since Q is a pmf, we know it sums to 1 so we get the same result replacing <math>(\frac{1}{exp(1-\beta)})</math> with <math>Pr(x^{(i)}</math>
Since Q is a pmf, we know it sums to 1 so we get the same result replacing <math>(\frac{1}{exp(1-\beta)})</math> with <math>P(x^{(i)}</math>
}}
}}


=====M-Step=====
=====M-Step=====
We will fix <math>Q</math> and maximize J wrt <math>\theta</math>
We will fix <math>Q</math> and maximize J wrt <math>\theta</math>
<math>J(\theta, Q) = \sum_{i=1}^{m} \sum_{j=1}^{m} Q^{(i)}_{(j)} \log \left( \frac{Pr(x^{(i)}, z^{(i)}=j;\theta)}{Q^{(i)}(j)} \right)</math><br>
<math>J(\theta, Q) = \sum_{i=1}^{m} \sum_{j=1}^{m} Q^{(i)}_{(j)} \log \left( \frac{P(x^{(i)}, z^{(i)}=j;\theta)}{Q^{(i)}(j)} \right)</math><br>
Assume <math>\Sigma_j = I</math> for simplicity.<br>
Assume <math>\Sigma_j = I</math> for simplicity.<br>
Then<br>
Then<br>
<math>
<math>
J(\theta, Q) = \sum_{i=1}^{m} \sum_{j=1}^{m} Q^{(i)}_{(j)} \log \left( \frac{Pr(x^{(i)}, z^{(i)}=j;\theta)}{Q^{(i)}(j)} \right)
J(\theta, Q) = \sum_{i=1}^{m} \sum_{j=1}^{m} Q^{(i)}_{(j)} \log \left( \frac{P(x^{(i)}, z^{(i)}=j;\theta)}{Q^{(i)}(j)} \right)
</math><br>
</math><br>
<math>
<math>
= \sum_{i=1}^{m} \sum_{j=1}^{m} Q^{(i)}_{(j)} \log ( Pr(x^{(i)}, z^{(i)}=j;\theta)) + C_1  
= \sum_{i=1}^{m} \sum_{j=1}^{m} Q^{(i)}_{(j)} \log ( P(x^{(i)}, z^{(i)}=j;\theta)) + C_1  
</math><br>
</math><br>
<math>
<math>
= \sum_{i=1}^{m} \sum_{j=1}^{m} Q^{(i)}_{(j)} \log ( Pr(x^{(i)} \mid z^{(i)}=j) Pr(z^{(i)}=j)) + C_1
= \sum_{i=1}^{m} \sum_{j=1}^{m} Q^{(i)}_{(j)} \log ( P(x^{(i)} \mid z^{(i)}=j) P(z^{(i)}=j)) + C_1
</math><br>
</math><br>
<math>
<math>
= \sum_{i=1}^{m} \sum_{j=1}^{m} Q^{(i)}_{(j)} \log ( Pr(x^{(i)} \mid z^{(i)}=j)) -  Q^{(i)}_{(j)} \log( Pr(z^{(i)}=j)) + C_1
= \sum_{i=1}^{m} \sum_{j=1}^{m} Q^{(i)}_{(j)} \log ( P(x^{(i)} \mid z^{(i)}=j)) -  Q^{(i)}_{(j)} \log( P(z^{(i)}=j)) + C_1
</math><br>
</math><br>
<math>
<math>
Line 172: Line 172:
Plugging in <math>\beta = -m</math> into our equation for <math>\phi_j</math> we get <math>\phi_j = \frac{1}{m}\sum_{i=1}^{m}Q^{(i)}_{(j)}</math>
Plugging in <math>\beta = -m</math> into our equation for <math>\phi_j</math> we get <math>\phi_j = \frac{1}{m}\sum_{i=1}^{m}Q^{(i)}_{(j)}</math>
}}
}}
==Generative Models==
Goal: Generate realistic but fake samples.
Applications: Denoising, impainting
===VAEs===
Variational Auto-Encoders<br>
[https://arxiv.org/abs/1606.05908 Tutorial]<br>
====KL Divergence====
* [[Wikipedia:Kullback–Leibler divergence]]<br>
* Kullback–Leibler divergence<br>
* <math>KL(P \Vert Q) =E_{P}\left[ \log(\frac{P(X)}{Q(X)}) \right]</math>
; Notes
* KL is always >= 0
* KL is not symmetric
* Jensen-Shannon Divergence
** <math>JSD(P \Vert Q) = \frac{1}{2}KL(P \Vert Q) + \frac{1}{2}KL(Q \Vert P)</math>
** This is symmetric
====Model====
Our model for how the data is generated is as follows:
* Generate latent variables <math>z^{(1)},...,z^{(m)} \in \mathbb{R}^r</math> iid where dimension r is less than n.
** We assume <math>Z^{(i)} \sim N(\mathbf{0},\mathbf{I})</math>
* Generate <math>x^{(i)}</math> where <math>X^{(i)} \vert Z^{(i)} \sim N(g_{\theta}(z), \sigma^2 \mathbf{I})</math>
** For some function <math>g_{\theta_1}</math> parameterized by <math>\theta_1</math>
====Variational Bound====
The variational bound is:
* <math>\log P(x^{(i)}) \geq E_{Z \sim Q_i}[\log P(X^{(i)} \vert Z)] - KL(Q_i(z) \Vert P(z))</math>
{{hidden | Derivation |
We know from Baye's rule that <math>P(z|X) = \frac{P(X|z)P(z)}{P(X)}</math>.<br>
Plugging this into the equation for <math>KL(Q_i(z) \Vert P(z|X))</math> yields our inequality.<br>
<math>KL(Q_i(z) \Vert P(z|X)) = E_{Q} \left[ \log(\frac{Q_i(z)}{P(z|X)}) \right]</math><br>
<math>=E_Q(\log(\frac{Q_i(z) P(X^{(i)})}{P(X_z)P(z)})</math><br>
<math>=E_Q(\log(\frac{Q_i(z)}{P(z)})) + \log(P(x^{(i)})) - E_Q(\log(P(X|z))</math><br>
<math>=KL(Q_i(z) \Vert P(z)) + \log(P(x^{(i)}) - E_Q(\log(P(X|z))</math><br>
Rearranging terms we get:<br>
<math>\log P(x^{(i)}) - KL(Q_i(z) \Vert P(z|X)) = E_Q(\log(P(X|z)) - KL(Q_i(z) \Vert P(z))</math><br>
Since the KL divergence is greater than or equal to 0, our variational bound follows.
}}
==GANs==
{{main | Generative adversarial network}}
===Wasserstein GAN===
[https://arxiv.org/abs/1701.07875 Paper]<br>
The main idea is to ensure the that discriminator is lipschitz continuous and to limit the lipschitz constant (i.e. the derivative) of the discriminator.<br>
If the correct answer is 1.0 and the generator produces 1.0001, we don't want the discriminator to give us a very high loss.<br>
====Earth mover's distance====
{{main | wikipedia:earth mover's distance}}
The minimum cost of converting one pile of dirt to another.<br>
Where cost is the cost of moving (amount * distance)<br>
Given a set <math>P</math> with m clusters and a set <math>Q</math> with n clusters:<br>
...
<math>EMD(P, Q) = \frac{\sum_{i=1}^{m}\sum_{j=1}^{n}f_{i,j}d_{i,j}}{\sum_{i=1}^{m}\sum_{j=1}^{n}f_{i,j}}</math><br>
;Notes
* Also known as Wasserstein metric
==Dimension Reduction==
Goal: Reduce the dimension of a dataset.<br>
If each example <math>x \in \mathbb{R}^n</math>, we want to reduce each example to be in <math>\mathbb{R}^k</math> where <math>k < n</math>
===PCA===
Principal Component Analysis<br>
Preprocessing: Subtract the sample mean from each example so that the new sample mean is 0.<br>
Goal: Find a vector <math>v_1</math> such that the projection <math>v_1 \cdot x</math> has maximum variance.<br>
Result: These principal components are the eigenvectors of <math>X^TX</math>.<br>
Idea: Maximize the variance of the projections.<br>
<math>\max \frac{1}{m}\sum (v_1 \cdot x^{(i)})^2</math><br>
Note that <math>\sum (v_1 \cdot x^{(i)})^2 = \sum v_1^T x^{(i)} (x^{(i)})^T v_1 = v_1^T (\sum x^{(i)} (x^{(i)})^T) v_1</math>.<br>
<!--
Thus our lagrangian is <math>\max_{\alpha} v_1^T (\sum x^{(i)} (x^{(i)})^T) v_1 + \alpha(\Vert v_1 \Vert^2 - 1)</math><br>
Taking the gradient of this we get:<br>
<math>\nabla_{v_1} (v_1^T (\sum x^{(i)} (x^{(i)})^T) v_1) + \alpha(\Vert v_1 \Vert^2 - 1)</math><br>
<math>= 2(\sum x^{(i)} (x^{(i)})^T) v_1 + 2\alpha v_1</math>
-->
===Kernel PCA===
{{main | Wikipedia: Kernel principal component analysis}}
===Autoencoder===
You have a encoder and a decoder which are both neural networks.